2018
DOI: 10.1111/1758-2229.12692
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic niche partitioning between suspended and sinking marine particles

Abstract: Summary Suspended particles are major organic carbon substrates for heterotrophic microorganisms in the mesopelagic ocean (100–1000 m). Nonetheless, communities associated with these particles have been overlooked compared with sinking particles, the latter generally considered as main carbon transporters to the deep ocean. This study is the first to differentiate prokaryotic communities associated with suspended and sinking particles, collected with a marine snow catcher at four environmentally distinct stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 101 publications
(153 reference statements)
5
74
3
1
Order By: Relevance
“…In our previous study we showed that bathypelagic prokaryotic communities were numerically dominated by taxa present in sunlit waters, so we attributed their pronounced changes with depth to shifts in the abundances of particle‐attached taxa during sinking as particle or surrounding environmental conditions change (Mestre et al., 2018). Accordingly, here we found that the surface‐related taxa present in the bathypelagic strongly reflected surface biotic gradients and were dominated by typical copiotrophic and eukaryote‐associated groups belonging to Actinobacteria, Alphaproteobacteria, Gammaproteobacteria and Flavobacteriia, in agreement with studies showing that that surface particles are first colonized by motile particle‐ or eukaryote‐associated specialists followed by other groups of copiotrophic taxa (Datta et al., 2016; Duret, Lampitt, & Lam, 2019; Fontánez et al., 2015; LeCleir, DeBruyn, Maas, Boyd, & Wilhelm, 2014; Pelve et al., 2017; Thiele, Fuchs, Amann, & Iversen, 2015). If many of these taxa thrive in the bathypelagic, particle sinking might be seeding deep‐sea assemblages with specific sets of microbial traits selected from within the pool of surface prokaryotes, perhaps explaining why deep‐sea prokaryotes seem more adapted to the attached lifestyle than surface ones (DeLong et al., 2006; Zhao, Baltar, & Herndl, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our previous study we showed that bathypelagic prokaryotic communities were numerically dominated by taxa present in sunlit waters, so we attributed their pronounced changes with depth to shifts in the abundances of particle‐attached taxa during sinking as particle or surrounding environmental conditions change (Mestre et al., 2018). Accordingly, here we found that the surface‐related taxa present in the bathypelagic strongly reflected surface biotic gradients and were dominated by typical copiotrophic and eukaryote‐associated groups belonging to Actinobacteria, Alphaproteobacteria, Gammaproteobacteria and Flavobacteriia, in agreement with studies showing that that surface particles are first colonized by motile particle‐ or eukaryote‐associated specialists followed by other groups of copiotrophic taxa (Datta et al., 2016; Duret, Lampitt, & Lam, 2019; Fontánez et al., 2015; LeCleir, DeBruyn, Maas, Boyd, & Wilhelm, 2014; Pelve et al., 2017; Thiele, Fuchs, Amann, & Iversen, 2015). If many of these taxa thrive in the bathypelagic, particle sinking might be seeding deep‐sea assemblages with specific sets of microbial traits selected from within the pool of surface prokaryotes, perhaps explaining why deep‐sea prokaryotes seem more adapted to the attached lifestyle than surface ones (DeLong et al., 2006; Zhao, Baltar, & Herndl, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Both endemic and surface‐related bathypelagic groups were present across all size fractions, so endemic particle‐attached prokaryotes might represent bathypelagic taxa that colonize older suspended particles resulting from the disaggregation of the sinking ones, or which might be autochthonously produced (Herndl & Reinthaler, 2013). In support of this hypothesis, microbial communities associated to suspended or sinking mesopelagic particles were found to differ in their structure, and the differences were attributed to variations in organic matter quality and freshness (Duret et al., 2019). In any case, the fact that even the structure and activity of free‐living bathypelagic communities retain a certain surface signature, coupled to the notion that particles are hotspots for microbial life and activity in the deep ocean (Bochdansky, Clouse, & Herndl, 2016; Herndl & Reinthaler, 2013), suggest that surface conditions play a key role in shaping the diversity and functioning of the bathypelagic microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…However, enteric bacteria are able to survive in seawater, particularly when organic material is readily available (Munro et al ., 1989). Settling was likely also a contributing factor, as many of the bacterial taxa that increased in relative abundance during storms and after soil addition to mesocosms are known to associate with sediment surfaces (DeLong et al ., 1993; Duret et al ., 2019) and some sedimentation was visible in mesocosm bottles despite using pumps to maintain water circulation. Moreover, tidal flushing may have transported introduced or resuspended bacteria offshore.…”
Section: Discussionmentioning
confidence: 99%
“…Flavobacteriaceae is a large and diverse family, although traits including gliding motility and the ability to degrade highmolecular-weight compounds, including chitin, a structural component in the copepod exoskeleton, are conserved throughout the order (Woese et al, 1990;Cottrell and Kirchman, 2000). Flavobacteriaceae are also abundant members of marine snow-associated microbial communities (Delong et al, 1993;Rath et al, 1998;Crump et al, 1999), suspended detrital particle communities (Duret et al, 2019) and also associate with phytoplankton (Grossart et al, 2005;Sapp et al, 2007).…”
Section: Discussionmentioning
confidence: 99%